The crystal structure of (bromido, chlorido)-tricarbonyl-(5,5′-dimethyl-2,2′-bipyridine)-rhenium(I), C15H12Br0.2Cl0.8N2O3Re1 - Moherane Lehlohonolo; Makhatshwa Marcus; Malan Frederick P.; Visser Hendrik G.; Manicum Amanda-Lee E. (Zeitschrift für Kristallographie - New Crystal Structures)
C15H12Br0.2Cl0.8N2O3Re1, monoclinic, P21/c (no. 14), a = 14.6713(4) Å, b = 11.4724(3) Å, c = 9.6206(3) Å, β = 106.592 (3), V = 1551.87(8) Å3, Z = 4, Rgt(F) = 0.0452, wRref(F2) = 0.1110, T = 149.99(10) K.